Study on the Structure and Performance of an Antagonistic Pneumatic Bidirectional Rotary Joint - Hongbo Liu (Hindawi Limited, 2021)
An antagonistic pneumatic bidirectional rotary flexible joint was developed to improve both safety and environmental adaptability of service robots and associated human interactions. The joint comprises two semicircular rotary actuators with positive and negative symmetrical distributions and a pneumatic brake. As such, it achieves forward and reverse rotations, and its damping and braking are adjustable in real time, enabling it to maintain its position. According to the force/torque balance at the free end of the rotary actuator, the rotation angle static model was established. The relationship between the actuator rotation angle, driving torque, impedance torque, and air pressure was obtained experimentally. The brake airbag was manufactured using additive manufacturing and silicone gel casting technologies. The mathematical model of the braking torque was established next, and the model was verified through experiments. Furthermore, an experimental system was constructed to carry out the air pressure-angle, air pressure-torque, and speed response experiments without the load on the joint. The results have shown that the joint can achieve any position within ± 68.5° when the driving air pressure varies from 0 to 0.30 MPa; the time required to reach the maximum angle was 0.85 s. The joint has shown good adjustable damping characteristics. Lastly, the braking torque reached 4.21 Nm at 0.32 MPa, effectively maintaining the position.